Fe / cuznal catalyst, preparation method thereof and application of Fe / cuznal catalyst in degradation of phenol-containing wastewater
Patent Information
- Application Number
- CN202410976139.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-07-19
AI Technical Summary
[0006]申请人在前期研究中,开发的层状双氢氧化物催化剂(CN106916054A)CuZnFeAl能有效催化苯酚制备苯二酚,然而该催化剂的活性组分是Cu2+,对含酚废水的降解处理效果有限
[0035] The Fe/CuZnAl catalyst prepared in this invention is a nanoscale layered hydroxide with a large specific surface area.
Smart Images

Figure CN118847124B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of green catalysis and environmental chemistry, specifically relating to an Fe / CuZnAl catalyst, its preparation method, and its application in the degradation of phenol-containing wastewater. Background Technology
[0002] Phenolic wastewater mainly originates from chemical processes such as coking, petrochemicals, coal chemicals, and fuel combustion. It is a stable and persistent pollutant. Without treatment, it can accumulate in the food chain and enter animals, plants, and humans, causing teratogenic, carcinogenic, and mutagenic effects, posing a significant threat to ecology and human health. Phenolic wastewater can be classified into monohydric phenols, polyhydric phenols, and CPs. Phenol wastewater is the most widespread and abundant among these wastewater types. As the most common organic pollutant in phenolic wastewater, phenol is the most concerning due to its high toxicity. Even at low concentrations, it is toxic, and its presence in natural water can also impact human health and the environment. Common methods for treating phenolic wastewater include physical, chemical, and biological methods.
[0003] However, commonly used physical methods such as adsorption for treating phenol-containing wastewater only transfer pollutants and do not achieve final disposal. Enzymatic degradation of phenol-containing wastewater has high requirements for equipment, temperature, pH, and other conditions, making it impractical (CN114941005B, CN 1134810016A). Chemical oxidation methods, especially advanced oxidation processes (AOPs), are efficient and low-cost wastewater treatment methods and have become a hot topic in organic wastewater degradation technology. Advanced oxidation processes (AOPs) utilize oxidants to generate highly oxidizing free radicals, which, in conjunction with catalysts, oxidize large organic molecules into smaller organic molecules, ultimately producing CO2 and H2O. The key to advanced oxidation processes lies in the development of highly efficient catalysts. Currently, new catalysts are still needed to achieve efficient treatment of phenol-containing wastewater.
[0004] In studies on the degradation of phenol-containing wastewater, montmorillonite, silica, Al2O3, and clay are the most common catalyst supports. CN113845201 prepared a Si-Fe / γ-Al2O3 catalyst to treat phenol-containing wastewater; with an initial pH of 3.5 and a reaction temperature of 30℃, the COD removal rate was 82.5%. Patent CN113546632A prepared a CeCu / AC catalyst to treat phenol wastewater; after 8.5 hours of degradation, the degradation rate remained around 93%. However, these catalysts still require improvement. Therefore, the development of more economical, green, and efficient degradation catalysts is urgently needed.
[0005] Layered double hydroxides possess considerable catalytic activity due to their ability to generate active material MOOH in situ, making them suitable as heterogeneous catalysts. Their advantages, including being green and clean, simple to prepare, and easy to separate and recover, have attracted significant attention. Layered double hydroxides also offer advantages such as low cost, convenient preparation, and structural variability, demonstrating broad practical application potential and continuously expanding the application fields of metal catalysts.
[0006] In its previous research, the applicant developed a layered double hydroxide catalyst (CN106916054A) CuZnFeAl, which can effectively catalyze the preparation of hydroquinone from phenol. However, the active component of this catalyst is Cu. 2+ However, its effect on the degradation and treatment of phenol-containing wastewater is limited. Summary of the Invention
[0007] To address the problems of the prior art, this invention aims to provide a Fe / CuZnAl layered metal hydroxide catalyst, its preparation method, and its application in the oxidative degradation of phenol-containing wastewater. By adjusting the active component of the catalyst to Fe, the applicant has achieved a high-efficiency catalytic degradation of phenolic substances using oxidants, with a degradation rate exceeding 98.5%. This catalyst is simple to prepare and inexpensive.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A Fe / CuZnAl catalyst is disclosed, wherein the Fe / CuZnAl catalyst is a layered hydroxide, and the molar ratio of the total Cu and Zn elements to Al elements in the Fe / CuZnAl catalyst is 3:1. This invention achieves an active component of Fe2O3 / Fe in the Fe / CuZnAl catalyst by adjusting the catalyst composition. 2+ .
[0010] Preferably, the molar ratio of Fe to the total amount of Cu, Zn, and Al in the Fe / CuZnAl catalyst is 5-30%:1. Most preferably, the molar ratio of Fe to the total amount of Cu, Zn, and Al in the Fe / CuZnAl catalyst is 12.5%:1.
[0011] The second objective of this invention is to provide a method for preparing the above-mentioned Fe / CuZnAl catalyst, comprising the following steps:
[0012] Solution A and solution B are mixed and reacted, then aged, and the resulting precipitate is the Fe / CuZnAl catalyst.
[0013] Solution A is Cu 2+ Zn 2+ Al 3+ and Fe 3+A mixed aqueous solution;
[0014] Solution B is CO3. 2- A mixed aqueous solution of OH- and OH-.
[0015] Preferably, the preparation method further includes the steps of washing, filtering, drying, and grinding the precipitate.
[0016] Preferably, the drying method is oven drying or freeze drying. The drying temperature is 80–110°C. The drying time is 12–24 hours.
[0017] Preferably, the Cu in solution A 2+ Zn 2+ Al 3+ or Fe 3+ It comes from the corresponding nitrate, chloride or sulfate.
[0018] Preferably, the CO3 in solution B 2- Derived from Na2CO3, OH - It is derived from NaOH.
[0019] Preferred, CO3 2- amount of substance The amount of substance n of OH- OH - Satisfies the following formula:
[0020]
[0021] in, Cu 2+ Zn 2+ The total amount of substance; For Al 3+ Fe 3+ The total amount of substance.
[0022] Preferably, the temperature of the mixing reaction is 55–65°C.
[0023] Preferably, the pH of the mixed reaction is 9 to 10.
[0024] Preferably, the aging temperature is 55–65°C.
[0025] Preferably, the aging time is 6 to 10 hours.
[0026] The third objective of this invention is to provide the application of the above-mentioned Fe / CuZnAl catalyst in the degradation of phenol-containing wastewater.
[0027] The application includes: using the Fe / CuZnAl catalyst to oxidize and degrade phenol-containing wastewater with an oxidant; the concentration of phenols in the phenol-containing wastewater is 100 mg / L to 1000 mg / L, preferably 260 mg / L to 340 mg / L, and optimally 280 mg / L to 300 mg / L.
[0028] Preferably, the oxidant is one of O2, air, ozone or H2O2.
[0029] Preferably, the mass ratio of the phenol-containing wastewater to the Fe / CuZnAl catalyst is 1000:0.2 to 1.6, more preferably 1000:0.5.
[0030] Preferably, the pH of the phenol-containing wastewater is 2 to 14, more preferably 6.
[0031] Preferably, the molar ratio of the oxidant to the phenolic hydroxyl groups in the phenol-containing wastewater is 2 to 14:1, more preferably 6:1.
[0032] Preferably, the oxidative degradation reaction takes 10 to 150 minutes, more preferably 60 minutes.
[0033] Preferably, the oxidative degradation reaction is carried out under stirring conditions. Preferably, the stirring speed is 300-800 r / min, wherein the optimal stirring speed is 450 r / min.
[0034] The beneficial effects of this invention are as follows:
[0035] The Fe / CuZnAl catalyst prepared in this invention is a nanoscale layered hydroxide with a large specific surface area.
[0036] (1) The active component of the catalyst of the present invention is Fe 3+ The active component is related to Cu 2+ Al 3+ Zn 2+ It forms a dense plate structure with O, so the active components will not be lost due to shedding or dissolution, and the catalyst can be recycled, which greatly saves raw material costs.
[0037] (2) The Fe / CuZnAl of the present invention belongs to the quaternary hydrotalcite, which has a layered structure and metallic bonds exist between the metal elements and between the metal and oxygen atoms.
[0038] (3) The catalyst of the present invention has a simple preparation process and low price, and has high atom economy.
[0039] (4) The catalyst of the present invention is easy to separate from the product after the catalytic oxidation and degradation reaction of phenol-containing wastewater is completed. Attached Figure Description
[0040] Figure 1 The image shows the XPS plot of the Fe / CuZnAl catalyst prepared in Example 1.
[0041] Figure 2 The image shows the EDS diagram of the Fe / CuZnAl catalyst prepared in Example 1.
[0042] Figure 3 The images show the XRD patterns of Fe / CuZnAl catalysts with different Fe contents prepared in Examples 1-4.
[0043] Figure 4 The images show the FT-IR spectra of Fe / CuZnAl catalysts with different Fe contents prepared in Examples 1-4.
[0044] Figure 5 SEM images of Fe / CuZnAl catalysts with different Fe contents prepared in Examples 1-4 are shown. Among them, (a) is 6.25% Fe / CuZnAl, (b) is 12.5% Fe / CuZnAl, (d) is 18.75% Fe / CuZnAl, and (e) is 25% Fe / CuZnAl.
[0045] Figure 6 The adsorption-desorption curves and pore size distribution diagrams of Fe / CuZnAl catalysts with different Fe contents prepared in Examples 1-4 are shown.
[0046] Figure 7 This is a diagram illustrating the degradation mechanism of the Fe / CuZnAl catalyst prepared in Example 1. Detailed Implementation
[0047] The present invention will now be described in more detail with reference to the embodiments, which do not limit the scope of protection of the present invention.
[0048] Example 1
[0049] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 2:1:1, 12.05g Cu(NO3)2·3H2O, 7.44g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 5.05g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0050] According to the formula It is calculated that 7.2g of NaOH and 7.94g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0051] Pre-fill a four-necked flask with approximately 10 mL of deionized water and heat to 55–65 °C. While stirring, simultaneously add solutions A and B to the flask, maintaining the pH of the mixture at 9–10 throughout the addition process. After addition is complete, continue stirring and age the solution at 60 °C for 6 hours. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate reaches 7. Then, dry the filtrate in an oven at 105 °C for 24 hours to obtain 12.5% Fe / CuZnAl-LDH, which is then ground into powder for later use. 12.5% represents the molar ratio of Fe to the total amount of Cu, Zn, and Al.
[0052] The XPS plot of the prepared 12.5% Fe / CuZnAl-LDH is shown below. Figure 1 As shown.
[0053] The EDS spectrum of the prepared 12.5% Fe / CuZnAl-LDH is shown below. Figure 2 As shown.
[0054] Catalyst performance evaluation: 0.25 g of 12.5% Fe / CuZnAl-LDH catalyst was used. 500 mL of a 300 mg / L phenol solution was added to the reaction vessel, along with 0.36 g of H₂O₂. The pH of the solution was adjusted to 6 using 1M sodium hydroxide or sulfuric acid solution. The reaction was started at 40 °C and stirred for 60 min. After the reaction, 3 mL of the sample was filtered through a 0.45 μm organic filter membrane and then mixed with an equal volume of ethanol solution at a 1:1 ratio. Gas chromatography showed a phenol degradation rate of 99.6%. To evaluate the repeatability of the catalyst, the reaction solution was centrifuged, washed, and dried in a vacuum drying oven after each experiment for use in the next reaction. The catalyst was reused 10 times, and the degradation rate remained approximately 98.7%. There was no significant decrease in catalyst activity or phenol degradation rate.
[0055] Example 2
[0056] The preparation of 6.25% Fe / CuZnAl-LDH is the same as in Example 1, except that the total molar ratio of Fe to Cu, Zn and Al is 6.25%.
[0057] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 2:1:1, 12.05g Cu(NO3)2·3H2O, 7.44g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 2.53g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0058] According to the formula It is calculated that 6.8g of NaOH and 6.625g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0059] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. Add solutions A and B to the flask simultaneously with stirring, maintaining the pH of the mixture at 9–10 throughout the dropwise addition. Continue stirring after the dropwise addition is complete and age the mixture at 60 °C for 6 hours. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 105 °C for 24 hours to obtain 6.25% Fe / CuZnAl-LDH, which is then ground into powder for later use.
[0060] The performance evaluation of the catalyst was the same as in Example 1, except that the iron ion content in the catalyst prepared in Example 2 was different, and the degradation rate of phenol was 89.7%.
[0061] Example 3
[0062] The preparation of 18.75% Fe / CuZnAl-LDH was the same as in Example 1, except that the total molar ratio of Fe to Cu, Zn and Al was 18.75%.
[0063] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 2:1:1, 12.05g Cu(NO3)2·3H2O, 7.44g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 7.58g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0064] According to the formula It is calculated that 7.6g of NaOH and 9.275g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0065] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. While stirring, add solutions A and B to the flask simultaneously, maintaining the pH of the mixture at 9–10 throughout the dropwise addition. Continue stirring after the addition is complete and age the mixture at 60 °C for 6 hours. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 105 °C for 24 hours to obtain 18.75% Fe / CuZnAl-LDH, which is then ground into powder for later use.
[0066] The performance evaluation of the catalyst was the same as in Example 1, except that the iron ion content in the catalyst was different, and the degradation rate of phenol was 95.2%.
[0067] Example 4
[0068] The preparation of 25% Fe / CuZnAl-LDH is the same as in Example 1, except that the total molar ratio of Fe to Cu, Zn and Al is 25%.
[0069] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 2:1:1, 12.05g Cu(NO3)2·3H2O, 7.44g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 10.1g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0070] According to the formula It is calculated that 8.0g of NaOH and 10.6g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0071] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. Add solutions A and B to the flask simultaneously with stirring, maintaining the pH of the mixture at 9–10 throughout the addition process. Continue stirring after the addition is complete and age the mixture at 60 °C for 6 hours. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 105 °C for 24 hours to obtain 25% Fe / CuZnAl-LDH, which is then ground into powder for later use.
[0072] The performance evaluation of the catalyst was the same as in Example 1, except that the iron ion content in the catalyst was different, and the degradation rate of phenol was 93.6%.
[0073] The XRD patterns of 6.25% Fe / CuZnAl-LDH, 12.5% Fe / CuZnAl-LDH, 18.75% Fe / CuZnAl-LDH and 25% Fe / CuZnAl-LDH prepared in Examples 1-4 are shown below. Figure 3 As shown.
[0074] The FT-IR spectra of 6.25% Fe / CuZnAl-LDH, 12.5% Fe / CuZnAl-LDH, 18.75% Fe / CuZnAl-LDH and 25% Fe / CuZnAl-LDH prepared in Examples 1-4 are shown below. Figure 4 As shown.
[0075] SEM images of the 6.25% Fe / CuZnAl-LDH, 12.5% Fe / CuZnAl-LDH, 18.75% Fe / CuZnAl-LDH and 25% Fe / CuZnAl-LDH prepared in Examples 1-4 are shown below. Figure 5 As shown. From Figure 5 As can be seen, particulate matter is attached to the surface of the catalyst's layered structure. This is iron oxide generated on the surface of the dense lamellar structure, which can further promote the degradation of phenolic substances.
[0076] The N2 adsorption-desorption and pore size distribution diagrams of 6.25% Fe / CuZnAl-LDH, 12.5% Fe / CuZnAl-LDH, 18.75% Fe / CuZnAl-LDH and 25% Fe / CuZnAl-LDH prepared in Examples 1-4 are shown below. Figure 6 As shown.
[0077] Example 5
[0078] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 1:2:1, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 5.05g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0079] According to the formula It is calculated that 7.2g of NaOH and 7.94g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0080] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. While stirring, add solutions A and B to the flask simultaneously, maintaining the pH of the mixture at 9–10 throughout the addition process. After the addition is complete, continue stirring and age the mixture at 60 °C for 6 hours. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 105 °C for 24 hours to obtain 12.5% Fe / CuZnAl-LDH1, which is then ground into powder for later use.
[0081] The performance evaluation of the catalyst was the same as in Example 1, and the degradation rate of phenol was 87.1%.
[0082] Example 6
[0083] The total molar ratio of Fe to Cu, Zn, and Al is controlled to be 6.25%. With a molar ratio of copper, zinc, and aluminum of 1:2:1 in the copper, zinc, aluminum, and iron salts, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 2.53g Fe(NO3)3·9H2O are weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0084] The mixed alkaline solution is the same as in Example 2.
[0085] The preparation of 6.25% Fe / CuZnAl-LDH1 was the same as in Example 5, except that the filter cake after filtration was placed in a freeze dryer and dried at -25°C for 12 hours.
[0086] The performance evaluation of the catalyst was the same as in Example 1, except that the oxidant was O3, and the degradation rate of phenol was 83.5%.
[0087] Example 7
[0088] The ratio of Fe to the total amount of Cu, Zn, and Al was controlled to be 18.75%.
[0089] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 1:2:1, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 7.58g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0090] The preparation of mixed alkaline solution B is the same as in Example 3.
[0091] The preparation of 18.75% Fe / CuZnAl-LDH1 was the same as in Example 5.
[0092] The performance evaluation of the catalyst was the same as in Example 1, except that the oxidant was O3, and the degradation rate of phenol was 80.5%.
[0093] Example 8
[0094] The total amount of Fe is controlled to be 25% of the total amount of Cu, Zn, and Al.
[0095] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 1:2:1, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 10.1g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0096] The preparation of mixed alkaline solution B is the same as in Example 4.
[0097] The preparation of 25% Fe / CuZnAl-LDH1 is the same as in Example 5.
[0098] The performance evaluation of the catalyst was the same as in Example 1, except that the oxidant was O3, and the degradation rate of phenol was 78.4%.
[0099] Example 9
[0100] 12.5% FeMgAl-LDH, 12.5% FeZnAl-LDH, 12.5% FeCuAl-LDH and 12.5% Fe / CuZnAl-LDH were prepared using the same method as in Example 1.
[0101] Catalyst performance evaluation:
[0102] The catalyst dosage was 0.25 g. 500 mL of a 300 mg / L phenol solution was added to the reaction vessel, along with 0.36 g of H₂O₂. The pH of the solution was adjusted to 6 using 1 M sodium hydroxide or sulfuric acid solution. The reaction was started at 40 °C and stirred for 60 min. After the reaction, 3 mL of the sample was filtered through a 0.45 μm organic filter membrane and then mixed with an equal volume of ethanol solution at a 1:1 ratio. The phenol degradation results were obtained by gas chromatography, as shown in Table 1.
[0103] Table 1 Effect of different catalytic materials on the catalytic degradation of phenol
[0104]
[0105]
[0106] As can be seen from Table 1, 12.5% Fe / CuZnAl-LDH exhibits the best catalytic degradation effect, which is due to the synergistic effect of various metal ions in the quaternary hydrotalcite.
[0107] Example 10
[0108] Catalyst performance evaluation: 0.25 g of the 2.5% Fe / CuZnAl-LDH catalyst prepared in Example 1 was used to treat 500 mL of 300 mg / L aqueous solutions of different phenols. The reaction temperature was 40 °C, the amount of hydrogen peroxide added was 0.36 g, and the reaction time was 60 min. After the reaction, samples were taken for analysis, and the degradation rates of phenols with different substituents are shown in Table 2. It can be seen from the table that the catalyst prepared in Example 1 achieved a degradation rate of over 90% for phenols.
[0109] Table 2 shows the degradation effect of phenols with different substituent groups in aqueous solution catalyzed by 12.5% Fe / CuZnAl-LDH catalyst.
[0110] 1 o-Cresol 60 95.1 2 m-Cresol 60 96.3 3 p-Cresol 60 93.7 4 hydroquinone 60 92.5 5 resorcinol 60 94.1 6 1,2,3-Phoroglossol 60 90.2 7 o-chlorophenol 60 90.5 8 m-Chlorophenol 60 97.6 9 phenol 60 98.7
[0111] The catalytic mechanism of Fe / CuZnAl catalyst for the degradation of phenolic compounds is as follows:
[0112] The possible catalytic mechanism by which Fe / CuZnAl-LDHs decrease the decomposition of phenol by oxidation in H2O2 is as follows: Figure 7 As shown, when Fe / CuZnAl-LDHs and H2O2 coexist, H2O2 is first adsorbed on the surface of the Fe / CuZnAl-LDHs catalyst, and then reacts with Fe... 3+ The reaction produces Fe 2+ And HO2·, formula (1). Fe 2+ It reacts with H2O2 to produce Fe 3+ And ·OH, formula (2). Due to the reaction under dark conditions, O2 - The source of · may be Fe 3+ It reacts with HO2· to produce Fe 2+ and O2 - ·, Equation (3), ·OH is generated through a disproportionation reaction. 1 O2, formula (4). ·OH and O2 produced in Fenton-like reactions. - ·、 1 Active substances such as O2 can degrade phenol in water into small molecules such as acetic acid through ring opening, and finally mineralize it into CO2 and H2O, as shown in equation (5).
[0113] H2O2 + Fe 3+ →Fe 2+ +HO2· (1)
[0114] H2O2 + Fe 2+ →Fe 3+ + ·OH (2)
[0115] Fe 3+ +HO2·→Fe 2+ +O2 - · (3)
[0116] ·OH+·OH→ 1 O2 + H2O (4)
[0117] (O2 - · / ·OH / 1 O2) + Phenol → CO2, H2O, acetic acid, etc. (5)
[0118] Example 11
[0119] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 1:2:1, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 2.02g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0120] According to the formula It is calculated that 6.72g of NaOH and 6.36g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0121] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. Add solutions A and B to the flask simultaneously with stirring, maintaining the pH of the mixture at 9–10 throughout the addition process. After the addition is complete, continue stirring and age the mixture at 60 °C for 10 h. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 110 °C for 12 h to obtain 5% Fe / CuZnAl-LDH1, which is then ground into powder for later use.
[0122] The performance evaluation of the catalyst was the same as in Example 1, and the degradation rate of phenol was 87.3%.
[0123] Example 12
[0124] With the molar ratio of copper, zinc, and aluminum in copper, zinc, aluminum, and iron salts being 1:2:1, 6.03g Cu(NO3)2·3H2O, 14.88g Zn(NO3)2·6H2O, 9.38g Al(NO3)3·9H2O, and 12.12g Fe(NO3)3·9H2O were weighed and dissolved in 100mL of deionized water to prepare mixed salt solution A.
[0125] According to the formula It is calculated that 8.32g of NaOH and 11.66g of Na2CO3 should be dissolved in 60mL of deionized water to prepare mixed alkaline solution B.
[0126] Pre-fill a four-necked flask with about 10 mL of deionized water and heat it to 55–65 °C. Add solutions A and B to the flask simultaneously with stirring, maintaining the pH of the mixture at 9–10 throughout the addition process. After the addition is complete, continue stirring and age the mixture at 60 °C for 10 h. After aging, filter the mixture and wash it with deionized water until the pH of the filtrate is 7. Then, dry it in an oven at 80 °C for 24 h to obtain 30% Fe / CuZnAl-LDH1, which is then ground into powder for later use.
[0127] The performance evaluation of the catalyst was the same as in Example 1, and the degradation rate of phenol was 89.1%.
[0128] Example 13
[0129] Referring to Example 1 of patent CN106916054A, a 150 mL NaOH alkaline solution with a molar concentration of 1 mol / L was prepared, denoted as solution A. 0.024 mol Cu(NO3)2·3H2O, 0.036 mol Zn(NO3)2·6H2O, 0.005 mol Fe(NO3)3·9H2O, and 0.015 mol Al(NO3)3·9H2O were dissolved in 150 mL deionized water and treated under ultrasonic conditions for 5 min to obtain a clear solution, denoted as solution B. Solutions A and B were simultaneously added dropwise to a 500 mL four-necked flask. During the addition, N2 protection was used and mechanical stirring was performed to control the pH of the system between 9 and 10. Finally, the pH of the system was maintained at 10. The system was dynamically crystallized in an oil bath at 60 °C for 6 h, and then microwave crystallized for 15 min (temperature maintained at 60 °C, microwave power controlled at 700 W). After centrifugation, the system was dried at 60 °C for 24 h to obtain a gray-black powder, which is the copper-based quaternary nano-hydrotalcite catalyst 42.86% CuZnFeAl.
[0130] Catalyst degradation performance evaluation: The catalyst dosage was 0.25 g of 42.86% CuZnFeAl, 500 mL of 300 mg / L phenol-water solution, reaction temperature was 40℃, hydrogen peroxide dosage was 0.36 g, and reaction time was 60 min. After the reaction, samples were taken for analysis. Because the phenol-containing wastewater contained a large amount of water, unlike patent CN106916054A, the reaction of hydrogen peroxide oxidizing phenol to produce hydroquinone and water was inhibited. Under the action of Fe element in the catalyst, the reaction yielded small molecule products of phenol degradation. Gas chromatography analysis showed that the phenol degradation rate was 47.28%.
Claims
1. The application of an Fe / CuZnAl catalyst in the degradation of phenol-containing wastewater, characterized in that, The Fe / CuZnAl catalyst is a layered hydroxide. The molar ratio of Cu and Zn to Al in the Fe / CuZnAl catalyst is 3:1; the molar ratio of Fe to the total amount of Cu, Zn, and Al in the Fe / CuZnAl catalyst is 5-30%:
1. The active component of the catalyst is Fe. 3+ ; The application includes using the Fe / CuZnAl catalyst to carry out an oxidative degradation reaction of phenol-containing wastewater with an oxidant. The oxidant is either ozone or H2O2.
2. The application according to claim 1, characterized in that, The molar ratio of Fe to the total amount of Cu, Zn, and Al in the Fe / CuZnAl catalyst is 12.5%:
1.
3. The application according to claim 1, characterized in that, The concentration of phenol in the phenol-containing wastewater is 100 mg / L to 1000 mg / L.
4. The application according to claim 3, characterized in that, The concentration of phenol in the phenol-containing wastewater is 260 mg / L to 340 mg / L.
5. The application according to claim 4, characterized in that, The concentration of phenol in the phenol-containing wastewater is 280 mg / L to 300 mg / L.
6. The application according to claim 1, characterized in that, The mass ratio of the phenol-containing wastewater to the Fe / CuZnAl catalyst is 1000:0.2~1.6, and the pH of the phenol-containing wastewater is 2~14.
7. The application according to claim 6, characterized in that, The mass ratio of the phenol-containing wastewater to the Fe / CuZnAl catalyst is 1000:0.5; the pH of the phenol-containing wastewater is 6.
8. The method for preparing the Fe / CuZnAl catalyst as described in claim 1, characterized in that, Includes the following steps: Solution A and solution B are mixed and reacted, then aged, and the resulting precipitate is the Fe / CuZnAl catalyst. Solution A is Cu 2+ Zn 2+ Al 3+ and Fe 3+ A mixed aqueous solution; Solution B is CO3. 2- and OH - A mixed aqueous solution.
9. The preparation method according to claim 8, characterized in that, Cu in solution A 2+ Zn 2+ Al 3+ or Fe 3+ The CO3 in solution B is derived from the corresponding nitrate, chloride, or sulfate. 2- Derived from Na2CO3, OH - It is derived from NaOH.
10. The preparation method according to claim 8, characterized in that, CO3 2- amount of substance and OH - amount of substance Satisfy the following formula: ; in, Cu 2+ Zn 2+ The total amount of substance; For Al 3+ Fe 3+ The total amount of substance.
11. The preparation method according to claim 8, characterized in that, The temperature of the mixing reaction is 55~65℃; the pH of the mixing reaction is 9~10; and the aging temperature is 55~65℃.
Citation Information
Patent Citations
Method of quickly and continuously preparing benzenediol from low-concentration water solution of phenol
CN106916054A
Catalyst for treating phenolic wastewater by wet oxidation method and preparation method of catalyst
CN113546632A
A recombinant expression vector, a genetically engineered bacterium that degrades phenol, and their applications
CN114941005B
Catalyst for treating organic wastewater and preparation method thereof
CN111514899A
Method for preparing cation defect type layered double hydroxide and application of cation defect type layered double hydroxide in preparation of high-valence iron ions
CN116119724A